There is no future without Native and Black faculty in higher education - Tachine, Amanda; Hailu , Meseret (Revista Española de Educación Comparada, 2023)
Using a letter-based methodology, we assert that higher education in the United States needs faculty members from Native and Black communities in order to be viable for presence and futures. We recognize that decolonization in higher education requires epistemological shifts that must be achieved by the people. Without people well-attuned to these epistemologies, such as critical Native and Black professors, this decolonization cannot happen. We also draw from extant literature and data from the National Center for Education Statistics to show how demographic disparities among faculty have been persistent over the past four decades. Throughout, we create a dialogue between decolonial and postcolonial literature. In doing so, we draw connections between these theories and education policies, practices, and pedagogies that advance more equitable and sustainable relationships in the relational flow of life where everyone and everything –both human and non-human–are deeply interconnected.